HE(II) PHOTOELECTRON-SPECTRA OF INDIUM(I) AND THALLIUM(I) HALIDES - Egdell, R; Orchard, A (1978)
Vapour phase He (II) photoelectron spectra of the thallium (I) and indium (I) halides MX (X = Cl, Br, I) are reported and compared with He (I) data. The additional structure in He (II) spectra is due largely to ionization of "inner" d electrons; the detail can be understood in terms of a weak-field perturbation of 2D5/2 and 2D 3/2 final states associated with a d9 configuration at the metal ion. However, the spectrum of TICI contains certain extra features which probably represent many-electron (or shake-up) processes.